2018
DOI: 10.1111/sms.13250
|View full text |Cite
|
Sign up to set email alerts
|

Participation in organized sports is associated with decreased likelihood of unhealthy lifestyle habits in adolescents

Abstract: Adolescence is a pivotal time for investing in both present and future health. Thus, it is important to identify arenas for promoting positive adolescent health behaviors and preventing negative ones. The aim of this study was to investigate the associations between organized sports participation (OSP) and a broad range of lifestyle habits in Norwegian adolescents. A comprehensive survey was completed by 13 269 junior high and high school students in southern Norway. Multivariable binary logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 47 publications
(129 reference statements)
5
44
3
3
Order By: Relevance
“…Because PA levels decrease while sedentary behaviors increase with age in Canadian girls, the finding that girls were active more frequently after FitSpirit participation is relevant [ 50 ]. The intervention had no impact on sleep duration, although sleep has previously been associated with physical activity [ 48 ]. This finding is probably due to the fact that FitSpirit mainly aims to increase physical activity in adolescent girls and does not address the theme of sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because PA levels decrease while sedentary behaviors increase with age in Canadian girls, the finding that girls were active more frequently after FitSpirit participation is relevant [ 50 ]. The intervention had no impact on sleep duration, although sleep has previously been associated with physical activity [ 48 ]. This finding is probably due to the fact that FitSpirit mainly aims to increase physical activity in adolescent girls and does not address the theme of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Associations among lifestyle habits have previously been studied in adolescents. Torstveit et al showed that participating in organized sports is inversely associated with sedentary behaviors, short sleep duration and unhealthful eating habits, such as irregular consumption of main meals and high intake of unhealthful food and beverages [ 48 ]. Active adolescents are more likely to engage in healthful dietary behaviors then their inactive peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the heterogeneity of measurements across studies, it is not possible to present cumulative results associated with each covariate in this review. Indeed, physically fit individuals are more likely to adopt a healthy living life-style that, accordingly, positively contribute to their gut microbiome composition and general health status [52]. Thus, controlling for PA-related baseline characteristics (behavioral factors such as depression or anxiety; levels of activity prior the intervention; PF levels; body composition, etc.)…”
Section: Body Composition and Health Characteristic Covariatesmentioning
confidence: 99%
“…Separating diet from PA (although distinct parameters) may not be feasible, as PA facilitates other positive factors (e.g., psychological and social benefits) [57]. It can be argued that PA it-self leads to dietary changes (eating less/more of specific food types, especially those perceived as "healthy") [52]. In order to address this issue, we encourage future researchers to account for additional effects of diet and closely monitor dietary changes, to mitigate possible effect of diet on gut microbiome composition.…”
Section: Diet and Nutritional Covariatesmentioning
confidence: 99%